Staying power - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
It s time to say goodbye and 'Thanks!' to a key person in the life of a Spore reader. After eleven and a half years heading the Publications Distribution Service, Nico Roskam has a new challenge: to open an information shop in Cameroon. He...